Comparative analysis of surfactant migrating asphalt in mixture under different temperatures - Meiyi Gao; Haitao Zhang; Yuping Feng; Song Zhao; Qianhui Zhang (Ain Shams Engineering Journal, 2023)
Water causes the asphalt to readily slip off the surface of the acid aggregate, causing fissures and compromising the structural stability of the asphalt pavement. In addition, fissures between asphalt and acid materials are difficult to cure in the presence of water. As a result, research into the healing of asphalt-acid aggregate fractures in the presence of water is necessary. This article incorporates a surfactant into the asphalt mixture. The application of surfactant “amphiphilic” properties to improve interfacial adhesion and healing between asphalt and acidic particles in moist environments. The molecular simulation approach was used in this study to create a microcrack model of asphalt-surfactant solution-acid aggregate to simulate crack healing at different temperatures. Prepare six sets of water containers for macro tests at the same time. The microscopic model's running results reveal that there is adsorption between asphalt and surfactant, surfactant and silica, and asphalt and silica surfaces, as well as changes in adsorption energy at different temperatures. Macroscopic investigations reveal that the addition of surfactants may improve asphalt adsorption on the surface of acidic aggregates in a wet environment, and the healing effect varies depending on the temperature, and the best healing temperature is 45 °C.